The Circadian Clock in the Regulation of Renal Rhythms. (December 2015) - Solocinski, Kristen; Gumz, Michelle L.
Since the kidney is integral to maintenance of fluid and ion homeostasis, and therefore blood pressure regulation, its proper function is paramount. Circadian fluctuations in blood pressure, renal blood flow, glomerular filtration rate, and sodium and water excretion have been documented for decades, if not longer. Recent studies on the role of circadian clock proteins in the regulation of a variety of renal transport genes suggest that the molecular clock in the kidney controls circadian fluctuations in renal function. The circadian clock appears to be a critical regulator of renal function with important implications for the treatment of renal pathologies, which include chronic kidney disease and hypertension. The development, regulation, and mechanism of the kidney clock are reviewed here.